Analysis of Turkey's hedging policy towards China : 2002-2015 - Guler, Muhammet Ali (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research examines Turkey's hedging policy towards China; 2002-2015. It argued that two issues (1) the Uighur issue and Turkey's pro-American Policy from 2002-2015 dominated Turkey's China policy. The study has employed hedging theory as its theoretical framework and used content analysis technique of qualitative research method. The data collected is discussed in chapters two, three and four with useful findings and recommendations discussed in chapter five. The study has concluded that the after the year 2000 political and economic relations between Turkey and China have improved steadily. Both countries have sincerely worked to improve bilateral relations. The study has also found that Uighur issue is not a real hurdle between Turkey and China while the Turkey's pro-American Policy has remained unchanged to date. The study highly recommends among others that Turkey should pursue a multi-dimensional policies and benefitting equally from its relations with China and the US.